2018
DOI: 10.1016/j.impact.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the in vitro genotoxicity of two rutile TiO2 nanomaterials in human intestinal and hepatic cells and evaluation of their interference with toxicity assays

Abstract: TiO 2 nanomaterials (NM) have a wide range of industrial applications, including their use in food products. The incorporation of these NMs in consumer products represents a clear concern for public health safety agencies and consumers, and further investigation of the potential impact of these products on human health is necessary. Indeed, since human oral exposure to TiO 2 NMs is expected to increase in the years to come, there exist legitimate concerns about the risk assessment of these nanomaterials presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 80 publications
4
26
1
Order By: Relevance
“…It was suggested that the transport mechanisms were disturbed by TiO 2 NM ingestion . This goes along with our findings, where decreased zinc and iron cellular concentrations were observed, even under nontoxic exposure conditions . Furthermore, the analysis of protein corona of TiO 2 NMs revealed different amounts of metal binding proteins (albumin, iron export ABC transporter ATPase, ovotransferrin, and tetranectin) and membrane transport proteins (solute carrier family) associated with NM surface (S 1).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…It was suggested that the transport mechanisms were disturbed by TiO 2 NM ingestion . This goes along with our findings, where decreased zinc and iron cellular concentrations were observed, even under nontoxic exposure conditions . Furthermore, the analysis of protein corona of TiO 2 NMs revealed different amounts of metal binding proteins (albumin, iron export ABC transporter ATPase, ovotransferrin, and tetranectin) and membrane transport proteins (solute carrier family) associated with NM surface (S 1).…”
Section: Resultssupporting
confidence: 86%
“…Visualization, internalization, and quantification of TiO 2 NMs were studied at a single cell level by means of IBM, ToF‐SIMS, and TEM techniques. Caco‐2 cells were exposed to the TiO 2 NMs at nontoxic conditions . Two different concentrations (20 and 100 µg mL −1 , corresponding to 4.7 and 24.4 µg cm −2 ) of hydrophobic NM103 or hydrophilic NM104 TiO 2 at two different time points (12 and 24 h) were chosen for IBM visualization and quantification.…”
Section: Resultsmentioning
confidence: 99%
“…The absence of cytotoxicity of the TiO 2 in Caco-2 cells is in agreement with previous reports [24,25,36,37]. Although Gerloff et al [36] and Dorier et al [24,37] did not use exactly the same benchmark NMs, they used TiO 2 very similar to ours.…”
Section: Cytotoxicitysupporting
confidence: 91%
“…In spite of many papers reporting the cytotoxicity assessment of TiO 2 in cells from GIT (see for example [24,25]), none has addressed and compared the effects upon digestion process of different crystalline TiO 2 forms in two distinct cell lines. A recent work studied the dissolution behavior, biodurability and persistence of several NMs (TiO 2 , SiO 2 , ZnO and Fe 2 O 3 ) in individual simulated gastrointestinal fluids (saliva, gastric and intestinal) and a physiologically relevant digestion cascade (saliva-gastric-intestinal), showing that TiO 2 was the most biodurable and persistent NM [26].…”
Section: Introductionmentioning
confidence: 99%
“…The human colorectal adenocarcinoma Caco-2 cell line was cultured (passages 25-38) until differentiation after 21 days as described in [40] including for cell seeding in various plate formats depending on the assay performed. Simarly, HepaRG cells (passages 13-19) were cultured and seeded for the various assays as previously described [40,41]. 10% FBS or William's medium + 5% FBS respectively.…”
Section: Cell Culture and Treatmentmentioning
confidence: 99%